Are we aware of neural activity in primary visual cortex? A neuropsychological case study - Hauw, Fabien; Sangaré, Aude; Munoz‐Musat, Esteban; Meyniel, Claire; Di Donato, Nina; Chokron, Sylvie; Bozon, Frédérique; Naccache, Lionel (Annals of clinical and translational neurology, 2024)
Objective According to a seminal hypothesis stated by Crick and Koch in 1995, one is not aware of neural activity in primary visual cortex (V1) because this region lacks reciprocal connections with prefrontal cortex (PFC). Methods We provide here a neuropsychological illustration of this hypothesis in a patient with a very rare form of cortical blindness: ventral and dorsal cortical pathways were lesioned bilaterally while V1 areas were partially preserved. Results Visual stimuli escaped conscious perception but still activated V1 regions that were functionally disconnected from PFC. Interpretation These results are consistent with the hypothesis of a causal role of PFC in visual awareness.